FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ASEPTOR METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI WILAYAH KERJA PUSKESMAS TANJUNG RAJA KABUPATEN OGAN ILIR - Jeni Malista; Siti Aisyah Hamid; Syarifah Ismed; Meriska Riski (Jurnal Kesehatan dan Pembangunan, 2023)
Family Planning (KB) is an action that helps married couples to avoid unwanted pregnancies, get the desired birth, regulate the interval between pregnancies, control the time of birth in a relationship with husband and wife and determine the number of children in the family. Population increase is a big problem in developing countries in the world, one of which is Indonesia which is a developing country with the largest population after China, India and the United States. The MKJP method is expected to regulate the rate of population growth. This type of research is quantitative using analytical survey methods, namely surveys or research that finds how and why health phenomena occur with a "Cross Sectional" approach where the independent variables (knowledge, husband's support, mother's attitude, parity, the role of health workers) and the dependent variable Long-Term Contraceptive Method (MKJP) Acceptors. The population in this study were active family planning acceptors in the Tanjung Raja Health Center from January to July 2021, opening 1809 people, stratified random sampling technique. The results of the study showed that there was a relationship between knowledge, husband's support, mother's attitude, parity, the role of health workers with Long Term Contraception Method Acceptors (MKJP). Suggestions are expected that health workers are expected to always provide counseling about contraception. and the role of midwives (p value = 0.038) with adherence to vitamin A consumption in the Talang Pangeran District Health Center Work Area. Ogan Ilir 2021.